Degradation of soybean meal proteins by wheat malt endopeptidase and the antioxidant capacity of the enzymolytic products - Fan, Jingxiao; Gao, Aiying; Zhan, Chao; Jin, Yuhong (Frontiers in Nutrition, 2023)
This study investigated the hydrolysis effect of the endopeptidase from wheat malt on the soybean meal proteins. The results indicated that the endopeptidase broke the peptide bonds of soybean meal proteins and converted the alcohol- and alkali-soluble proteins into water-soluble and salt-soluble proteins. In addition, wheat malt endopeptidase did not break the disulfide bonds between proteins but affected the conformation of disulfide bonds between substrate protein molecules, which were changed from the gauche-gauche-trans (g-g-t) vibrational mode to the trans-gauche-trans (t-g-t) vibrational mode. Wheat malt endopeptidase exhibited the highest enzymatic activity at 2 h of enzymatic digestion, demonstrating the fastest hydrolytic rate of soybean meal proteins. Compared with the samples before enzymatic hydrolysis, the total alcohol- and alkali-soluble proteins were decreased by 11.89% but the water- and salt-soluble proteins were increased by 11.99%, indicating the hydrolytic effect of endopeptidase. The corresponding water-soluble proteins had molecular weights of 66.4-97.2 kDa, 29-44.3 kDa and 20.1 kDa, while the salt-soluble proteins had molecular weights of 44.3-66.4 kDa, 29-44.3 kDa and 20.1 kDa, respectively. The degree of enzymatic hydrolysis of soybean meal reached the maximum at 8 h. The newly created proteins exhibited significantly antioxidant properties, which were inversely related to the molecular weight. Proteins with molecular weight <3 kDa had the highest antioxidant performance with an antioxidant capacity of 1.72±0.03 mM, hydroxyl radical scavenging rate of 98.04%, and ABTS (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) radical scavenging capacity of 0.44±0.04 mM.